Greater Cognitive-Motor Interference in Individuals Post-Stroke During More Complex Motor Tasks. Issue 1 (January 2022) - Rice, Jordyn; Corp, Daniel T.; Swarowsky, Alessandra; Cahalin, Lawrence P.; Cabral, Danylo F.; Nunez, Christina; Koch, Sebastian; Rundek, Tatjana; Gomes-Osman, Joyce
Abstract : Background and Purpose: Dual-task (DT) walking assessments allow for the simultaneous evaluation of cognitive and motor performance. During DT walking, individuals may experience interference in one or both tasks, known as cognitive-motor interference (CMI). The primary purpose of this study was to compare CMI between individuals post-stroke and healthy persons group during single- and dual-motor and cognitive tasks, using 2 distinct walking tasks. Methods: Motor performance was quantified as the total time for the Timed Up and Go (TUG) and gait speed for the 90-second walk (90W). Cognitive performance was measured as the correct response rate (CRR) during serial 7 subtractions. Participants performed the motor and cognitive tasks in isolation for the single-task (ST) and simultaneously for DT conditions, TUG-DT and 90W-DT. A repeated-measures analysis of variance assessed group (poststroke and healthy) by condition (ST and DT) interactions for the TUG, 90W, and CRR. Results: There were significant main effects of group and condition for both the TUG and the 90W ( P < 0.05). There was also an interaction effect for the TUG, with individuals post-stroke demonstrating a larger decrement in TUG-DT performance compared with healthy persons ( P < 0.05). Furthermore, a significant interaction effect was observed for the CRR, in which healthy individuals exhibited a greater decrement in performance from the ST to the 90W-DT ( P < 0.05). Discussion and Conclusions: Individuals post-stroke were susceptible to greater motor interference during the more complex motor task, the TUG-DT. However, the only decrements observed in cognitive performance from the ST to DT occurred in healthy individuals during the 90W-DT. Video Abstract available for more insights from the authors (see the Video, Supplemental Digital Content 1, available at: http://links.lww.com/JNPT/A367 ). Abstract : Supplemental Digital Content is Available in the Text.